Composite submental flaps in facial reconstructive surgery involving the zygoma and orbit - Khan, Usman (J Otolaryngol Head Neck Surg, 2020)
BACKGROUND: The submental island flap (SIF) is a reliable option for reconstructing defects in the facial region and offers several advantages when compared to free-flap alternatives. While the reconstructive applications of the SIF have been demonstrated in the lower face, there are limited reports on its utility as a composite flap for reconstructing defects of the upper facial skeleton. To our knowledge, we report the first cases of composite (osteocutaneous) SIFs used for reconstruction of complex facial defects involving the zygoma and lateral orbit respectively. CASE PRESENTATIONS: Three consecutive cases are presented. All were performed following resection of skin cancers with invasion of the upper facial skeleton. The first case was a 68-year-old male with a longstanding history of non-melanoma skin cancers who presented with a 7 cm recurrent basal cell carcinoma (BCC) with bicortical invasion of the left zygoma. The second case was an 88-year-old female with several squamous cell carcinomas (SCC), including a dominant 7.1 cm SCC on the right temple with orbital invasion. A third case was a 75-year-old immunosuppressed male with a 6.5 cm SCC of the right cheek with invasion of the orbit and zygoma following prior resection as well as high dose radiotherapy. The operative management of all cases involved harvesting the SIF on its vascular pedicle alongside the inferior portion of the mandible with rigid fixation to address the bony defects. The first case was robust throughout adjuvant radiotherapy with no flap complications after 2 year follow up. The second patient received adjuvant radiation therapy to an area that was previously radiated. Although the flap remained viable for a year, the patient experienced delayed soft tissue loss over the bony segment and eventual devitalization of the distal flap. The third case achieved a satisfactory result with no complications. CONCLUSIONS: Our case series outlines a unique application of the composite (osteocutaneous) submental island flap (SIF) for reconstruction of complex facial defects involving the upper facial skeleton. The osteocutaneous SIF should be used with caution in patients receiving adjuvant radiotherapy who have a history of previous radiation to the same or overlapping field. GRAPHICAL ABSTRACT: [Image: see text]